Cognitive decline associated with anesthesia and surgery in the elderly: does this contribute to dementia prevalence?. Issue 3 (May 2017) - Evered, Lisbeth; Scott, David A.; Silbert, Brendan
Abstract : Purpose of review: To provide an update on the current state of research investigating the effects of anesthesia and surgery on cognition in the elderly, including consideration of overlap with cognitive disorders in the community. Recent findings: The studies reviewed here identify detrimental effects of anesthesia and surgery on cognition in a proportion of elderly individuals. Animal models demonstrate an association between anesthetic agents and Alzheimer's disease pathology. Human studies demonstrate a high incidence of cognitive impairment preoperatively in the elderly and further decline postoperatively, with recent work showing that poor preoperative cognitive function is a key predictor for further postoperative decline. Results from retrospective studies into an association between Alzheimer's disease and prior anesthesia and surgery are equivocal, but there are some data to suggest an association with accelerated cognitive decline in the long term. Postoperative delirium is common and even in individuals with normal preoperative cognition is associated with long-term decline. Summary: Cognitive impairment in the elderly ultimately leads to a decline in function with high personal and societal costs. Following anesthesia and surgery, decline in cognition is observed in some individuals, which may represent vulnerability for future decline or may alter their cognitive trajectory. Recent work suggests factors that impact this decline and/or impair recovery include higher risk patients and subtle cognitive impairment preoperatively. Identifying these individuals is critical to determining opportunities for intervention and preventive strategies, and ultimately reducing the impact on functional decline. It remains unclear if anesthesia and surgery play a role in the onset or progression of mild cognitive impairment and dementia across the community. Recent work showing that preoperative impairment is a significant risk factor for decline indicates that routinely assessing cognition preoperatively would allow improved management including referral pathways for patients at risk, delirium prevention, specifically optimizing care and consideration of treatment options.